A Transnational Perspective of the Evolution of Rosa Luxemburg's Theory of The Mass Strike. Issue 2 (3rd April 2018) - Bies, John D.
Abstract : Rosa Luxemburg was one of the most significant political theorists within the Socialist International movement during the turn of the nineteenth century. Her career included writings addressing various political issues such as nationalism and Marxist orthodoxy. One of her more significant approaches to revolutionary strategy was the use of mass strikes to attack both political and economic national institutions as a means for bringing down imperialistic capitalism. This article examines, from a transnational perspective, the development of her acclaimed The Mass Strike, the Political Party and Trade Unions (1906). Specifically, four "geo-moments" were used to analyse how her conception of mass strikes evolved from her early roles as a strike organiser in Warsaw to participation and assessment of the 1905 Russian Revolution that resulted in her Mass Strike pamphlet.